The Tax Treatment of Government Bonds - Norregaard, John (IMF Working Papers; Working Paper ;, 1997)
In their effort to finance fiscal deficits at a reasonable cost, governments compete with other users of financial capital. Governments, however, are in the unique position that they are the only debt suppliers that can determine the taxation of debt instruments they issue. Following an overview of the current tax treatment of government bonds in OECD countries, this paper argues that-on purely economic grounds-there are no reasons for exempting interest on government bonds. Administrative difficulties in capturing interest on many other debt instruments in the tax net may, however, provide a rationale for doing so.